ELEARNING APPLICATION DESIGN COMPUTER TUTORIAL BASED WEBSITE USING PHP & MySQL - Siswanto Siswanto; Erick Orlando, SKom, MMSI (Jurnal Sistem Informasi, 2009)
Along with the development of Information and Communication Technology (ICT)which grew rapidly and needs someone to obtain information on expected the sooner.Computer as one tool producer of information, makes the existence of these toolsbecomes important. To support the computer as producing information requiredmeans of learning for computer science itself.Therefore the writer feels it will be necessary means of electronic learning(eLearning) to meet the information needs of computer science. With this application,eLearning Computer-based tutorials website someone who needs information can getcomputer science quickly without limitation of time and place. With this simplicity isexpected can increase the quantity and quality of a person in the development oftechnology existing information.